Poverty and the Spatial Distribution of Rural Population - Barbier, Edward B.; Hochard, Jacob P. (World Bank Group, Washington, DC, 2014)
According to global spatial data sets in 2000 more than one-third of the rural population in developing countries was located on less favored agricultural land and areas. Less favored agricultural lands are susceptible to low productivity and degradation, because their agricultural potential is constrained biophysically by terrain, poor soil quality, or limited rainfall. Less favored agricultural areas include less favored agricultural lands plus favorable agricultural land that is remote, that is, land in rural areas with high agricultural potential but with limited access. The paper presents tests of whether these spatial distributions of rural population influence poverty directly or indirectly via income growth in 83 developing countries from 2000 to 2012. The analysis finds no evidence of a direct impact on poverty, but there is a significant indirect impact via the elasticity of poverty reduction with respect to growth. Reducing poverty requires targeting rural populations in less favored lands and remote areas, in addition to encouraging out-migration in some areas.